Efficiency in water and nutrient use in treated wastewater for three horticultural crops - Silva Santos, Roberta Daniela; Muniz Ventura, Kevim; Henryque Costa de Souza, MARCELLO; Máximo Sanchéz Román, Rodrigo (Revista Geama, 2024)
Irrigated agriculture primarily aims to maximizing crop productivity. One way to achieve this goal is through the use of treated wastewater (TWW). The objectives of this study were to evaluate the productivity of lettuce, beet, and radish irrigated with wastewater treated by a septic tank system (SODIS + 125 mg.L-1 H2O2) (TWWS) and constructed wetlands (TWWCW); calculate the amounts of macronutrients nitrogen (N), phosphorus (P), and potassium (K) supplied through irrigation; and assess the effect of irrigation with TWWS and TWWCW on water use efficiency. The experiment was conducted under field conditions at the Faculty of Agronomic Sciences - UNESP, Botucatu, SP. Lettuce and beet productivity was higher when cultivated with TWWCW compared to TWWS, showing an increase of 8.5% (75% TWWCW) and 30.8% (100% TWWCW), respectively. For radish, productivity was higher with TWWS compared to TWWCW, providing an increase of 19.7% (50% TWWS). Regarding nutrient input from TWWS and TWWCW, they partially met the nutritional needs, supplying more than 70% of the nitrogen demand of the vegetables. For lettuce and radish, the highest Water Use Efficiency – Irrigation (WUEI) and Water Use Efficiency – Irrigation + Precipitation (WUEIP) values were obtained through irrigation with TWWS, providing a minimum increase of 15% in the final productivity of the vegetables. In beet, the highest WUEI and WUEIP values were obtained through irrigation with TWWCW, providing a minimum increase of 50% in the final productivity.